Literature Review of Sets-Based Practical Guidelines (Science, Environment, Technology and Society) to Improve Concept Understanding and Scientific Process Skills - Salsabilla Rahmadhani; Tri Ariani (Transpublika Publisher, 2025)
Concept understanding and science process skills are essential abilities that students must possess to achieve success in science learning. These abilities help students understand scientific phenomena, think logically, and apply concepts in everyday life. However, several studies show that students’ concept understanding and science process skills are still relatively low. This issue arises because the teaching materials used in schools have not fully connected scientific concepts with real-life contexts, making learning tend to be theoretical and less meaningful. One solution to address this problem is to develop SETS-based teaching materials (Science, Environment, Technology, and Society) that can link scientific concepts with environmental, technological, and social aspects. This study uses a literature review method by analyzing previous studies indexed in Sinta 2-4 from 2015 to 2025 that are relevant to the theme and research questions. Based on the review of 50 selected articles, it was found that the development of SETS-based teaching materials can significantly improve students’ concept understanding and science process skills, making learning more contextual and meaningful.